2009
DOI: 10.1016/j.jvs.2009.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of upper arm transposed arteriovenous fistulae and upper arm prosthetic grafts

Abstract: Transposed arteriovenous fistulas have significantly higher primary and secondary patency rates, require fewer revisions, and are less likely to develop a significant infection than AVG. This study supports the contention that as long as a patient is a candidate for a tAVF based on anatomic criteria, a tAVF should be considered before an AVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…To this end, Dialysis Outcome Quality Initiative (DOQI) has issued guidelines regarding the preference for AVF construction when feasible (6). Well-developed AVFs demonstrate significant advantages compared with prosthetic bridge grafts when comparisons between rates of patency and infection are performed (7). Those benefits notwithstanding, a suboptimal fistula that cannot be consistently and reliably accessed will require the prolonged usage of an indwelling tunneled CVC, a factor that increases the potential for catheter-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, Dialysis Outcome Quality Initiative (DOQI) has issued guidelines regarding the preference for AVF construction when feasible (6). Well-developed AVFs demonstrate significant advantages compared with prosthetic bridge grafts when comparisons between rates of patency and infection are performed (7). Those benefits notwithstanding, a suboptimal fistula that cannot be consistently and reliably accessed will require the prolonged usage of an indwelling tunneled CVC, a factor that increases the potential for catheter-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Woo et al [8] showed in his research about comparison between autogenous arteriovenous fistula using venous transposition and linear shaped prosthetic graft that autogenous fistula was better than prosthetic graft in both primary(48% vs. 14%) and secondary(57% vs. 19%) patency rate at 5-year. In addition, revision frequency for secondary patency was significantly lower in autogenous arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Once functional, AVFs have better patency rates and fewer complications than arteriovenous grafts and hemodialysis catheters. (1, 2) Nevertheless, newly created AVFs are susceptible to primary failure. This common complication is defined as the AVF that never matures to support cannulation with 2 hemodialysis needles, or fails within the first 3 months after its initial cannulation.…”
Section: Introductionmentioning
confidence: 99%